Interaction of the endogenous antibody response with activating FcγRs enhance control of Mayaro virus through monocytes. - Megan M Dunagan; Nathânia Dábilla; Colton McNinch; Jason M Brenchley; Patrick T Dolan; Julie M Fox (PLoS Pathogens)
Mayaro virus (MAYV) is an emerging arbovirus. Previous studies have shown antibody Fc effector functions are critical for optimal monoclonal antibody-mediated protection against alphaviruses; however, the requirement of Fc gamma receptors (FcγRs) for protection during natural infection has not been evaluated. Here, we showed mice lacking activating FcγRs (FcRγ-/-) developed prolonged clinical disease with increased MAYV in joint-associated tissues. Viral reduction was associated with anti-MAYV cell surface binding antibodies rather than neutralizing antibodies. Lack of Fc-FcγR engagement increased the number of monocytes present in the joint-associated tissue through chronic timepoints. Single-cell RNA sequencing showed elevated levels of pro-inflammatory monocytes in joint-associated tissue with increased MAYV RNA present in FcRγ-/- monocytes and macrophages. Transfer of FcRγ-/- monocytes into wild type animals was sufficient to increase virus in joint-associated tissue. Overall, this study suggests that engagement of antibody Fc with activating FcγRs promotes protective responses during MAYV infection and prevents a pro-viral role for monocytes.